Kishmish - Sami, Mustafa; Shireen, Syed (book group Karachi, 1992)
Through simple language and vibrant illustrations, the book introduces young readers to basic Urdu vocabulary and sentence structure. The story promotes kindness, empathy, and the importance of friendship.